Comparison of Selenium Nanoparticles and Sodium Selenite on the Alleviation of Early Atherosclerosis by Inhibiting Endothelial Dysfunction and Inflammation in Apolipoprotein E-Deficient Mice - Junying Xiao (MDPI AG, 2021)
Atherosclerosis and related cardiovascular diseases represent the greatest threats to human health, worldwide. Previous animal studies showed that selenium nanoparticles (SeNPs) and Na2SeO3 might have anti-atherosclerotic activity, but the underlying mechanisms are poorly elucidated. This study compared the anti-atherosclerotic activity of SeNPs stabilized with chitosan (CS-SeNPs) and Na2SeO3 and the related mechanism in a high-fat-diet-fed apolipoprotein E-deficient mouse model of atherosclerosis. The results showed that oral administration of both CS-SeNPs and Na2SeO3 (40 μg Se/kg/day) for 10 weeks significantly reduced atherosclerotic lesions in mouse aortae. Mechanistically, CS-SeNPs and Na2SeO3 not only alleviated vascular endothelial dysfunction, as evidenced by the increase of serum nitric oxide level and the decrease of aortic adhesion molecule expression, but also vascular inflammation, as evidenced by the decrease of macrophage recruitment as well as the expression of proinflammatory molecules. Importantly, these results were replicated within in-vivo experiments on the cultured human endothelial cell line EA.hy926. Overall, CS-SeNPs had a comparable effect with Na2SeO3 but might have more potential in atherosclerosis prevention due to its lower toxicity. Together, these results provide more insights into the mechanisms of selenium against atherosclerosis and further highlight the potential of selenium supplementation as a therapeutic strategy for atherosclerosis.